INTERNALISASI NILAI SOPAN SANTUN MELALUI PELAJARAN PKN DI MIS BIDAYATUL HIDAYAH - Nurul Miftahul Awaliyah Harahap (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
Abstract: The purpose of the study was to photograph the guidance of manners ethics in students in civics learning in class V MIS Bidayatul Hidayah, since the teacher designed the learning, carried out PPKn learning, evaluated the manners behavior of students, and the response of students to the guidance of manners carried out by teachers through PPKn learning. in-depth interviews and documentation (artipak). The object of the study is the ongoing civics learning activities. The subjects of the study were class teachers, parents, peers and principals. The data collection instrument is the researcher himself with the help of observation guidelines and interview guidelines. The data is analyzed narratively with in-depth meaning. The conclusions of the research results indicate (1) civics learning designs made by teachers using the 2013 curriculum guidelines. The teacher first analyzes KD and KI first. The RPP used is sourced from a handbook or teacher's guide without a mission analysis of the values and behaviors expected from KD and KI. (2) when learning is carried out the teacher has carried out the guidance of manners behavior. Teachers have been able to motivate learners to behave in good manners; (3) evaluation of the results of the guidance of manners behavior has not been formally programmed, evaluation is still focused on the evaluation of cognitive aspects, (4) students have responded positively and actively to fostering manners behavior.